Trangene Inheritance in Transgenic Wheat - Zainudin Basri (Jurnal Matematika & Sains, 2005)
The achievement in genetic transformation is not only determined by the success in integrating transgenes into the plant genome, but also by the ability of transgenes to be stably expressed in the following generations. Transgenes integrated into trangenic wheat obtained via microprojectile bombardment method could be transmitted and, in most cases, expressed until the third generation as demonstrated in this study. The expression of the GUS gene was stable as observed in leaves, microspores, anthers, ovaries and seeds. Nevertheless, the bar gene appeared to undergo a reduction or disappearance in expression in a number of plants from the first to the third generation.